"Ledre Super" Supply Chain Performance Measurement Using The Supply Chain Operation Reference (SCOR) Method : (Case Study of Home Industry Moro Tresno) - Ilmi Nurul Istiqomah; Rizky Stighfarrinata; Ardana Putri Farahdiansari (Journal of Social Science and Economics, 2022)
Supply Chain Management (SCM) is a system that involves the process of producing, storing, shipping, distributing and selling products to meet the demand for these products into the hands of consumers. This research was conducted in a home industry, namely the home industry of Moro Tresno. Moro Tresno's home industry has a variety of products marketed, but researchers only conduct research on super ledre products. This company has a major problem faced by is how to respond to orders from consumers. The company has not been able to fulfill when there is an increase in orders during the holiday season and approaching holidays. From a normal order of 9,900 packs, it can increase up to 80% to 17,820 packs. This supply chain performance measurement uses the SCOR method by applying 4 attributes, namely, reliability, responsiveness, agility, and asset management, and weighted by the pairwise comparison method. The data collection process was carried out by interviewing the home industry owner Moro Tresno because it was believed to be able to provide correct and accurate information. The total value of performance is 95.36. Dimensions that need improvement are reliability and agility. Recommendations for improving the reliability dimension RL.2.3 Accuracy of documentation by making tables neater. Meanwhile, RL.2.4 Perfect condition by analyzing seven tools to find out the cause and follow up on product damage and reliability in delivery. Improvement of agility AG.2.1 Days to meet the increase in production carried out socialization of craftsmen, selecting craftsmen according to performance, recruiting new craftsmen and giving awards to craftsmen.